Factors influencing spinal curvature measurements on ultrasound images for children with adolescent idiopathic scoliosis (AIS) - Zheng, Rui (PLoS One, 2018)
The measurements of spinal curvatures using the ultrasound (US) imaging method on children with scoliosis have been comparable with radiography. However, factors influencing the reliability and accuracy of US measurement have not been studied. The purpose of this study is to investigate the effects of curve features and patients’ demographics on US measurements and to determine which factors influence the reliability and accuracy. Two hundred children with scoliosis were recruited and scanned with US by one experienced operator and three trainees. One experienced rater measured the proxy Cobb angles from US images twice one week apart and compared the results with clinical radiographic records. The correlation and accuracy between the US and radiographic measurements were subdivided by different curve severities, curve types, subjects’ weight status and US acquisition experiences. A total of 326 and 313 curves were recognized from radiographs and US images, respectively. The mean Cobb angles of the 13 missing curves were 17.4±7.4° and 11 at the thoracic region. Among the 16 curves showing large discrepancy (≥6°) between US and radiographic measurements, 7 were main thoracic and 6 were lumbar curves. Twelve had axial vertebral rotation (AVR) greater than 8°. The US scans performed by the experienced operator showed fewer large discrepancy curves, smaller difference and higher correlation than the scans from the trainees (3%, 1.7±1.5°, 0.95 vs 6%, 2.4±1.8°, 0.90). Only 4% missing and 5% large discrepancy curves were demonstrated for US measurements in comparison to radiography. The missing curves were mainly caused by small severity and in the upper spinal region. There was a higher chance of the large discrepancy curves in the main thoracic and lumbar regions with AVR>8°. A skilled operator acquired better US images and led to more accurate measurements especially for those subjects with larger curvatures, AVR and body mass index (BMI).